PENGARUH PRAKTIK PENGHINDARAN PAJAK, MANAJEMEN LABA, KOMISARIS INDEPENDEN, DAN KOMITE AUDIT TERHADAP NILAI PERUSAHAAN (Studi pada Perusahaan Property, Real Estate, and Building Construction yang terdaftar di BEI periode 2015-2019) - Arif Setiawan; R.Ery Wibowo A.S; Nurcahyono . (Universitas Muhammadiyah Semarang, 2021)
The purpose of this study was analyzed the effect of tax avoidance, earnings management, independent commissioners, and audit committee on firm value. This research used a quantitative approach with the type of comparative causal research. The research was conducted on the property, real estate, and building construction companies listed on the Indonesia Stock Exchange in 2015-2019 with a total sample of 185 samples using the purposive sampling method. The data collection method is a documentation study with secondary data taken from the Indonesia StockExchange website. This study used multiple linear regression analysis techniques. Tax avoidance is calculated using the Cash Effective Tax Rate (CETR) ratio. Earnings management measured using discretionary accruals which are calculated using the modified Jones method. Independentcommissioners are calculated using the percentage of the number of independent commissioners to the board of commissioners. The Audit Committee is calculated by the number of members of the audit committee. The results of this study indicate that tax avoidance, earnings management, independent commissioners, and the audit committee have a positive influence on firm value. Recommendations for future research to expand the object of research beyond property, real estate, and building construction companies. Future studies can use other calculation models forthe dependent variable and the independent variable.